Assimilation of L2 vowels to L1 phonemes governs L2 learning in adulthood: a behavioral and ERP study - Grimaldi, Mirko; Sisinni, Bianca; Gili Fivela, Barbara; Invitto, Sara; Resta, Donatella; Alku, Paavo; Brattico, Elvira (Frontiers in Human Neuroscience, 2014)
According to the Perceptual Assimilation Model (PAM), acoustic similarity/dissimilarity between sounds of the second language (L2) and the native language (L1) governs L2 learnability in adulthood and predicts L2 sound perception by naïve listeners. We performed behavioral and neurophysiological experiments on two groups of university students at the first and fifth years of the English language curriculum and on a group of naïve listeners. Categorization and discrimination tests, as well as the mismatch negativity (MMN) brain response to L2 sound changes, showed that the discriminatory capabilities of the students did not significantly differ from those of the naïve subjects. In line with the PAM model, we extend the findings of previous behavioral studies showing that, at the neural level, classroom instruction in adulthood relies on assimilation of L2 vowels to L1 phoneme categories and does not trigger improvement in L2 phonetic discrimination.